2021
DOI: 10.1002/dmrr.3465
|View full text |Cite
|
Sign up to set email alerts
|

Central obesity, smoking habit, and hypertension are associated with lower antibody titres in response to COVID‐19 mRNA vaccine

Abstract: Aims To explore variables associated with the serological response following COVID‐19 mRNA vaccine. Methods Eighty‐six healthcare workers adhering to the vaccination campaign against COVID‐19 were enrolled in January–February 2021. All subjects underwent two COVID‐19 mRNA vaccine inoculations (Pfizer/BioNTech) separated by 3 weeks. Blood samples were collected before the 1st and 1–4 weeks after the second inoculation. Clinical history, demographics, and vaccine side eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
235
9
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(291 citation statements)
references
References 30 publications
42
235
9
5
Order By: Relevance
“…The presence of comorbidities may impair the anticipated immunogenicity following COVID-19 vaccination [30][31][32][33]. Relatively lower NAbs titers were observed among individuals with diabetes at D22.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of comorbidities may impair the anticipated immunogenicity following COVID-19 vaccination [30][31][32][33]. Relatively lower NAbs titers were observed among individuals with diabetes at D22.…”
Section: Discussionmentioning
confidence: 99%
“…These increased risks have been found after adjusting for age, ethnicity, income, and other demographic and socio-economic factors [ 6 ]. Notably, individuals with central obesity had lower antibody titers than those without, after two COVID-19 mRNA vaccine inoculations (Pfizer/BioNTech) separated by 3 weeks, which would unfavorably affect their prognosis in the case of vaccine breakthrough [ 7 ].…”
mentioning
confidence: 99%
“…A certain underdetection of cases among smokers could not be ruled out, since they may develop lower antibody levels. 31 However, a recent review concluded that smokers have lower risk of infection, 32 although the mechanisms are not well understood. 33 A lower probability of participation of infected smokers in our study due to their higher risk of hospitalization is unlikely, as we contacted each person up to 3 times -one per round-, so they had several chances to participate.…”
Section: Discussionmentioning
confidence: 99%